Batasan Riba, Gharar, dan Maisir (Isu Kontemporer Dalam Hukum Bisnis Syariah) - Zulfahmi, Zulfahmi; Maulana , Nora (Syarah: Jurnal Hukum Islam dan Ekonomi, 2022)
The original law in muamalah is permissible. Islam gives freedom to its people to innovate in doing business or dealing with other people in terms of muamalah. However, the principle of freedom must comply with the recommendations and leave the prohibitions. Among the prohibitions in Islamic economic transactions are gharar, gambling, and usury, namely transactions that are expressly prohibited by the Qur'an and hadith. Because the treatment is classified as an act of vanity. Allah has commanded buying and selling and forbidden usury, just as Allah has forbidden the deceptive consumption of human money, and Allah has encouraged reciprocal trading (mutual benefit). The majority of scholars, from classical scholars to modern scholars, agree that this practice is prohibited. This prohibition is also intended so that property is not lost and to eliminate situations that create hostility between the people who transact.